Assessment of Cognitive Impairment in Survivors of Breast Cancer: A cross-sectional study: Chemobrain em Câncer de Mama - Pedras, Renata Nunes (2022)
Prospective and cross-sectional study to determine the prevalence of cognitive impairment resulting from chemotherapy, and to explore predictors and mediators in survivors of breast cancer. We used the Distress Thermometer, Hospital Anxiety and Depression Scale, Functional Assessment of Chronic Illness Therapy-General and Functional Assessment of Cancer Therapy-Cognitive Function. Survivors (N = 62) reported a high prevalence of distress (46.8%) and anxiety (24.2%), with low scores on cognitive deficit and cognitive skills perceived subscales. Cognitive functioning was associated with age (B = 1.42; p = 0.002), professional performance (B = -23.12; p = 0.004), depression (B = -5.43; p = 0.001), and quality of life (B = 1.24; p = 0.001). Cognitive impairment must be considered in Psycho-Oncology service.